Targeting inflammatory macrophages with hyaluronan tetrasaccharide: effects on fibroblast collagen degradation and synthesis - Uno, Eiko; Kim, Florence; Yoshino, Mihoko; Sato, Yasunari; Hashimoto, Masao; Watanabe, Kenji; Mizukami, Yoichi; Muto, Jun (Frontiers in Immunology, 2025)
Hyaluronan (HA) provides moisturizing benefits and exhibits unique biological activities based on its molecular weight. While the anti-inflammatory effects of high-molecular-weight HA have been well studied, the impact of hyaluronan tetrasaccharide (HA4), an ultralow-molecular-weight HA, on the skin immune system is not fully understood. Thus, we investigated how HA4 affects the differentiation of M1 macrophages, which increase during photoaging. As a result, we added HA4 during the M1 macrophage differentiation phase and conducted a gene expression analysis. HA4 partially decreased the transition from M0 to M1 macrophages and reduced the expression of proinflammatory cytokines like IL-6. However, the M2 marker IL-1ra increased, while IL-10 levels remained constant, suggesting that HA4 does not fully polarize macrophages toward the M2 phenotype. Normal human dermal fibroblasts (NHDF) were treated with an M1 macrophage-conditioned medium (M1-CM) and a modified version containing HA4 (M1+HA4-CM). The M1+HA4-CM notably decreased the expression of IL-6 and IL-8, along with the collagen-degrading enzyme MMP1. Collagen synthesis assays showed that HA4 helped restore collagen fiber formation. Moreover, RNA-seq analysis of NHDF treated with the conditioned medium confirmed that M1+HA4-CM amplified the expression of genes related to collagen production while decreasing collagen-degrading enzyme gene expression. Neutralization assays employing a TLR4 antibody suggested that decreasing IL-6 in NHDF by HA4 may be independent of the TLR4 signaling pathway. HA4 is vital in partially suppressing M1 macrophage differentiation and the release of inflammatory factors, as well as regulating collagen remodeling in NHDF. These findings indicate that HA4 holds promise as a molecule for mitigating inflammation-induced collagen degradation by modulating macrophage activity in photoaged skin.